Cover Image. (26th April 2018) - Gao, Xia; Ma, Yuling; Wang, Zhuowei; Bia, Ruibin; Zhang, Pei; Hu, Fangdi
Abstract : The cover image, by Xia Gao et al., is based on the Research Article Identification of anti‐inflammatory active ingredients from Tumuxiang by ultra‐performance liquid chromatography/quadrupole time‐of‐flight‐MS E, DOI:10.1002/bmc.4179 .